Interdiffusion of InxGa1-xAs/InP Quantum Well Structures Induced by Proton Implantation - Paulus L. Gareso (Institut Teknologi Bandung, 2009)
We have investigated the atomic intermixing of InxGa1-xAs/InP quantum well structures induced by proton implantation using photoluminescence. Photoluminescence results showed that energy shift was systematically increased as doses increased. As the dose further increased, Saturation in energy shift was observed. At elevated temperature irradiation revealed that the magnitude of the energy shift decreased as the irradiation increased followed by a broadening of the PL linewidth and reduction of the PL intensity. This indicated that dynamic annealing and mobility of the defects play an important role in the type and concentration of residual defects.